(untitled) (Research, Society and Development, 2025)
The expansion of new agricultural frontiers constitutes a key factor in the interaction between society and nature, profoundly influencing emerging territorial dynamics and driving the intensive use of technologies aimed at increasing production. Currently, these areas are consolidating as hubs of expression within the technical-scientific informational environment, as productive processes invigorate not only the exploited areas but also surrounding territories. In this context, the present study examines the dynamics of land use and land cover in the Itapecuruzinho Stream sub-basin for the years 2003, 2013, and 2023. The research aims to understand the main aspects, patterns of land use and cover, and the agents involved in this transformative process. The analysis reveals a significant territorial reconfiguration over the study period. The integration of geotechnologies with data from collection 9.0 of the MapBiomas project enabled an in-depth spatiotemporal analysis of the sub-basin, allowing for the monitoring of the agricultural frontier expansion phenomenon in the region.